Fast Peel‐Off Ultrathin, Transparent, and Free‐Standing Films Assembled from Low‐Dimensional Materials Using MXene Sacrificial Layers and Produced Bubbles. Issue 3 (23rd December 2021) - Ling, Zheng; Wang, Fuqiang; Shi, Changrui; Wang, Zhiyu; Fan, Xuanhui; Wang, Lu; Zhao, Jiafei; Jiang, Lanlan; Li, Yanghui; Chen, Cong; Tang, Dawei; Song, Yongchen
Abstract: Ultrathin, transparent, and free‐standing films assembled from low‐dimensional nanomaterials (LDMs) are promising for various applications, including transparent heaters and membranes. However, the intact separation of the assembled films, especially those with controlled ultrathin thickness from deposited substrates, is a tremendous challenge, particularly for fast peeling off via self‐detaching. Herein, we propose a versatile method to rapidly peel off ultrathin assembled LDM films, including three types of carbon nanotubes, vermiculite, Ag nanowires, and carbon nanotube@graphene, by dissolving the MXene interlayer from the layer‐by‐layer filtered MXene/LDM Janus films using diluted H2 O2 . The MXene sacrificial interlayers play dual roles, including physical isolation of LDM films from filter membranes and the production of bubbles that buoy ultrathin LDM films, making them free‐standing. The integrality and self‐detaching rate of the LDM films are determined by the loading and reactivity of the MXene interlayers. The intact LDM films can self‐detach in 80 s by dissolving the optimized MXene interlayer and producing bubbles. The as‐made free‐standing ultrathin LDM films can be transferred to arbitrary substrates and exhibit outstanding performance as transparent heaters. This scalable method provides an efficient and versatile method to produce ultrathin, transparent, and free‐standing LDM films and finds new applications for the growing MXene family. Abstract : A versatile method is developed to rapidly peel off ultrathin and transparent films assembled from various low‐dimensional materials (LDMs) by bubble buoying and dissolving the MXene interlayer from the layer‐by‐layer filtered MXene/LDM Janus films using diluted H2 O2 . The integrality and self‐detaching rate of the LDM films are determined by the loading and reactivity of MXene.